Selective hydrolysis preparation method of PHS resin for photoresist
By using MOFs as catalysts for selective hydrolysis reactions, the problem of low selectivity of PHS resin hydrolysis process in photoresist is solved, efficient catalysis and low-cost production are achieved, and the quality of photoresist is improved.
Patent Information
- Application Number
- CN202411819855.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
AI Technical Summary
The hydrolysis process of PHS resin in existing photoresist is low, which makes it difficult to purify product impurities and the catalyst use efficiency is low, which increases production costs.
Using metal organic framework materials (MOFs) as catalysts, polyparaacetoxystyrene and its copolymers are converted into polyparahydroxystyrene and its copolymers through selective hydrolysis reactions, improving the selectivity and efficiency of the hydrolysis reaction.
It realizes efficient catalysis and selective hydrolysis, which reduces impurities in the product, reduces post-treatment costs, and improves the quality of photoresist.
Smart Images

Figure CN119462995A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photoresist materials, and in particular relates to a method for preparing a novel PHS resin for photoresist. Background Art
[0002] In recent years, the development trend of chip manufacturing in the world has been to develop in a reverse direction of globalization. Europe, the United States, China, Japan and South Korea are all striving to build independent supply of the entire industry chain. Among them, photoresist is known as the "pearl" in the crown of chip manufacturing and is a field with extremely high technological content. my country's weaknesses in the field of photoresist are concentrated in the mid-to-high-end fields, including: KrF, ArF, and EUV photoresist fields. Among them, KrF photoresist is mainly composed of para-hydroxystyrene and its copolymer resin (PHS resin), and photoacids, solvents, and other additives are auxiliary materials.
[0003] PHS resins can be obtained by hydrolyzing poly(p-acetoxystyrene) or poly(p-acetoxystyrene) copolymers by using a catalyst. There are two types of catalysis: homogeneous catalysis and heterogeneous catalysis.
[0004] Homogeneous catalysis mostly uses acid or base for catalysis. Its disadvantages are: 1. The photoresist requires extremely high purity, and the catalyst is dissolved in the reaction solution. During the precipitation process, the by-products or catalysts are wrapped by polymers and become impurities. They need to be purified through neutralization, multi-stage filtration, multiple dissolution and precipitation processes. Photoresist resin has extremely high requirements for metal ion impurities. All post-processing requires electronic grade solvents. More post-processing results in greater costs. 2. A large amount of catalyst is required, and the catalyst needs to be added during the reaction, which has low efficiency. 3. The catalytic selectivity is poor, resulting in the decomposition of non-target groups.
[0005] Zheng Xiangfei (Journal of Polymer Research, 2017, 24 (11), 198 (1-7).) et al. used sodium methoxide as a catalyst for hydrolysis, resulting in a lot of metal ions in the product. Ion exchange resin A15 was needed to remove the metal ions, which was costly and complicated and not suitable for mass production. Hiroshi Ito (Journal of Photopolymer Science and Technology, 1994, 7 (3): 433-447.) et al. used weak alkaline ammonia water for hydrolysis, but the alkalinity of ammonia water was too weak, requiring excessive ammonia water (target group: catalyst molar ratio was 1: 5-10), and the catalytic efficiency was low. Wang Liyuan (Chinese patent, CN105669889B, 2018.11-6) et al. used hydrochloric acid for hydrolysis, resulting in the hydrolysis of tert-butyl acrylate, etc., and could not achieve selective hydrolysis, so the scope of use was narrow.
[0006] The catalyst of heterogeneous catalysis is insoluble in the reaction solution and can be removed by filtration and other methods, and it is easy to regenerate and reuse the catalyst. However, at present, only Ran Ruicheng (Chinese patent, CN1300187C, 2007.2-14) et al. use polymer carrier catalysts for hydrolysis reactions. The disadvantage is that the product resin is also a polymer, and during the use of the polymer carrier catalyst, it is inevitable that some polymers will dissolve in the reaction solution. This part of impurities cannot be removed, which greatly affects the quality of the photoresist.
[0007] MOFs is a super-porous nanomaterial, a crystalline powder full of tiny molecular-sized holes. It has a unique structure: a porous crystal structure in which metals are interconnected by organic connectors. Therefore, it not only has a crystalline structure similar to the regular pores of zeolite molecular sieves, but also has a higher specific surface area than traditional porous materials. If you expand the surface area within one gram of MOFs, it covers the entire football field. Due to the presence of organic components, it also has the characteristics of designability, tailorability, adjustable pore size, and easy functionalization of the pore surface. MOFs can be used in many fields such as separation and adsorption, energy storage, efficient catalysis, solidification of carbon dioxide, electrode materials, and biomedicine.
[0008] Based on the above problems and technological development, we decided to develop a heterogeneous catalytic method combining metal organic framework materials (MOFs materials) as catalysts to prepare poly (p-hydroxystyrene) and its copolymer resins, mainly targeting common PHS resins such as p-acetoxystyrene monomers, binary copolymers of p-acetoxystyrene and styrene, binary copolymers of p-acetoxystyrene and acrylates, terpolymers of p-acetoxystyrene, styrene and acrylates, and terpolymers of p-acetoxystyrene, 1-(1-ethoxyethoxy)-4-vinylbenzene and (4-vinylphenyl) tert-butyl carbonate. Summary of the invention
[0009] In order to solve the above problems, the present invention provides a method for preparing PHS resin for photoresist by selective hydrolysis. The inventors use MOFs materials as catalysts to selectively hydrolyze poly(p-acetoxystyrene) and its copolymers to obtain poly(p-hydroxystyrene) and its copolymers, so as to solve the problems of low selectivity of the hydrolysis process and difficulty in purifying product impurities in the current route.
[0010] The present invention provides the following technical solutions:
[0011] A method for preparing a PHS resin for photoresist by selective hydrolysis comprises the following steps:
[0012] Step 1, adding poly(p-acetoxystyrene) or poly(p-acetoxystyrene) copolymer, MOFs catalyst, water and solvent into a reactor to obtain a mixed solution;
[0013] Step 2, at room temperature, initially mechanically stir the mixed solution obtained in step 1, introduce nitrogen into the system for purging, mechanically stir for 2 h-3 h under nitrogen purging, increase the mechanical stirring speed, and heat the system to the reaction temperature;
[0014] Step 3, after the reaction is completed, the reaction solution is filtered under reduced pressure to obtain a filtrate, and the obtained filtrate is slowly dripped into pure water, the product is slowly precipitated, and the pure water is under mechanical stirring;
[0015] Step 4: After the reaction liquid is added, the precipitate is obtained and stirring is continued for 2 h.
[0016] Step 5, filtering the precipitate under reduced pressure, taking the filter residue, and drying it in a vacuum oven to obtain a pure white product poly(p-hydroxystyrene) and its copolymer resin, and performing characterization tests on the product.
[0017] Beneficial Effects
[0018] Compared with the prior art, the preparation method provided by this application has the following beneficial effects:
[0019] ① High-efficiency catalysis: The high specific surface area of MOFs allows more active sites to combine with raw materials, enhancing catalytic ability; the porous structure facilitates the transfer of electrons and substances. It greatly increases the catalytic effect and catalytic speed of the catalyst, and the catalytic reaction can be completed at an equivalent of 0.1%-0.5%.
[0020] ② Selective hydrolysis: Amine or sulfonic acid MOFs will preferentially hydrolyze poly(p-acetoxystyrene) and are inert to the alkoxy groups on the SP3 hybrid. The metal framework structure of MOFs contains many unsaturated metal sites, which release electrons, so they are more active on the SP2 hybrid aryl groups and can be selectively hydrolyzed. In the experiment, the selective hydrolysis of the copolymer of p-acetoxystyrene and acrylates showed that poly(p-acetoxystyrene) was completely hydrolyzed into poly(p-hydroxystyrene), while the polyacrylate component was well preserved.
[0021] ③ Reduce impurities in finished products, improve product quality, reduce post-processing, and reduce costs: MOFs, as an organic-inorganic hybrid crystal material, will not dissolve slightly like polymer catalysts, and will not be separated from the reaction liquid by filtration like acids and bases. MOFs also have a certain adsorption effect. By-products can be adsorbed in the lattice, thereby reducing by-product impurities in the product, avoiding the use of a large amount of electronic-grade solvents in post-processing, and reducing costs.
[0022] ④ Recycling and cost reduction: MOFs are non-polymer carrier catalysts and can be separated from the reaction liquid by filtration. They will not remain in the solution. The separated MOFs can be activated and used again. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The NMR characterization results of the product prepared in Example 1 of the present application are shown;
[0024] Figure 2 The infrared spectrum characterization results of the product prepared in Example 1 of the present application are shown;
[0025] Figure 3 The gel chromatography characterization results of the product prepared in Example 1 of the present application are shown;
[0026] Figure 4 The NMR characterization results of the product prepared in Example 2 of the present application are shown;
[0027] Figure 5 The infrared spectrum characterization results of the product prepared in Example 2 of the present application are shown;
[0028] Figure 6 The gel chromatography characterization results of the product prepared in Example 2 of the present application are shown;
[0029] Figure 7 The NMR characterization results of the product prepared in Example 3 of the present application are shown;
[0030] Figure 8 The infrared spectrum characterization results of the product prepared in Example 3 of the present application are shown;
[0031] Fig. 9 The gel chromatography characterization results of the product prepared in Example 3 of the present application are shown;
[0032] Fig.10 The NMR characterization results of the product prepared in Example 4 of the present application are shown;
[0033] Fig.11 The infrared spectrum characterization results of the product prepared in Example 4 of the present application are shown;
[0034] Fig.12 The gel chromatography characterization results of the product prepared in Example 4 of the present application are shown. DETAILED DESCRIPTION
[0035] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0036] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0037] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0038] An embodiment of the present application provides a method for preparing a PHS resin for photoresist by selective hydrolysis, the method comprising the following steps:
[0039] Step 1, adding poly(p-acetoxystyrene) or poly(p-acetoxystyrene) copolymer, MOFs catalyst, water and solvent into a reactor to obtain a mixed solution;
[0040] Step 2, at room temperature, initially mechanically stir the mixed solution obtained in step 1, introduce nitrogen into the system for purging, mechanically stir for 2 h-3 h under nitrogen purging, increase the mechanical stirring speed, and heat the system to the reaction temperature;
[0041] Step 3, after the reaction is completed, the reaction solution is filtered under reduced pressure to obtain a filtrate, and the obtained filtrate is slowly dripped into pure water, the product is slowly precipitated, and the pure water is under mechanical stirring;
[0042] Step 4: After the reaction liquid is added, the precipitate is obtained and stirring is continued for 2 h.
[0043] Step 5, filtering the precipitate under reduced pressure, taking the filter residue, and drying it in a vacuum oven to obtain a pure white product poly(p-hydroxystyrene) and its copolymer resin, and performing characterization tests on the product.
[0044] In one embodiment, the poly(p-acetoxystyrene) copolymer includes: a p-acetoxystyrene monomer, a binary copolymer of p-acetoxystyrene and styrene, a binary copolymer of p-acetoxystyrene and acrylate, a terpolymer of p-acetoxystyrene, styrene and acrylate, and a terpolymer of p-acetoxystyrene, 1-(1-ethoxyethoxy)-4-vinylbenzene and tert-butyl (4-vinylphenyl) carbonate.
[0045] In one embodiment, the MOFs catalyst is an amino MOFs catalyst and a sulfonic acid MOFs material, including: MOF-808-NH2, NH2-Uio-66, Mil-101-Cr-NH2, NH2-UIO-66 (Hafnium), MIL-101 (Cr) -SO3H, UIO-66-SO3H.
[0046] In one embodiment, the solvent in step 1 is an electronic grade solvent including: methanol, ethanol, isopropanol, tetrahydrofuran, tert-butyl methyl ether, n-heptane, cyclohexane, toluene, xylene, ethyl acetate, DMF, DMSO, and NMP.
[0047] In one embodiment, the molar ratio of the poly(p-acetoxystyrene) or poly(p-acetoxystyrene) copolymer, the MOFs catalyst, pure water, and the solvent is 1:0.1%-0.5%:1:5-10.
[0048] In one embodiment, the mechanical stirring speed under nitrogen purge in step 2 is 47-54 rpm, and the mechanical stirring speed after increasing the mechanical stirring speed is 295-305 rpm; the mechanical stirring speed of pure water during precipitation in step 3 is 22-28 rpm.
[0049] In one embodiment, the reaction temperature in step 2 is 50°C-80°C.
[0050] In one embodiment, the pure water is electronic grade pure water, which is distilled in a laboratory with a cleanliness level of 1,000 for future use, and needs to be deoxygenated before use to ensure that the dissolved oxygen content in the water is extremely low.
[0051] One embodiment of the present application provides a poly(p-hydroxystyrene) for photoresist and a copolymer resin thereof obtained according to the preparation method.
[0052] An embodiment of the present application provides an application of the poly(p-hydroxystyrene) and its copolymer resin in the preparation of photoresist.
[0053] In the examples of the present application, for the sake of completeness of the preparation route, Step 1 mainly involves the preparation methods of several polymers, and the focus of the present application is on the application of MOFs.
[0054] Example 1
[0055] Step 1: Place 100g of p-acetoxystyrene in a 2L four-necked bottle equipped with a condenser, a thermometer, a nitrogen inlet, and an electric stirrer, and add 4g of AIBN (azobisisobutyronitrile) and 450g of ethanol. After stirring for two hours under nitrogen protection, heat to 70°C and keep the temperature for 18 hours. Dissolve, precipitate, and filter to obtain a crude white precipitate, which is p-acetoxystyrene monomer.
[0056] Step 2: Add the above white precipitate, 10g pure water and 1.5mg NH2-UiO-66 to another four-necked bottle, stir for 2.5h under nitrogen protection, set the speed to 50 rpm, gradually increase the speed to 300 rpm, and heat the reaction to 50°C. After 10 hours, take a liquid sample for Fourier infrared absorption spectrum test. The analysis results show that the hydrolysis reaction reaches 99%. After the reaction is completed, cool to 25-35°C and filter to remove NH2-UiO-66 (can be recovered). Characterization results refer to Figure 2
[0057] Step 3: Drop the filtrate into pure water to precipitate a white precipitate, stir mechanically at a speed of 25 rpm, and filter under reduced pressure to obtain a solid white product. Pulp it with pure water three times, filter and dry it to obtain the final product. Nuclear magnetic hydrogen spectrum test analysis shows that poly(p-acetoxystyrene) undergoes hydrolysis reaction, and the product is consistent with the target product. The characterization results can be found in Figure 1 . Through GPC test, the product Mw = 10515, PDI = 1.525. The yield is 95%. The characterization results are shown in Figure 3 .
[0058] Example 2
[0059] Step 1: Put 94g of p-acetoxystyrene and 6g of tert-butyl acrylate into a 2L four-necked bottle equipped with a condenser, a thermometer, a nitrogen inlet, and an electric stirrer, and add 4g of AIBN (azobisisobutyronitrile) and 450g of ethanol. After stirring for two hours under nitrogen protection, heat to 70°C and keep the temperature for 18 hours. Dissolve, precipitate, and filter to obtain a white precipitate, which is a binary copolymer of p-acetoxystyrene and acrylate.
[0060] Step 2: Add the above white precipitate, 10g pure water and 1.4mg NH2-UiO-66 to another four-necked bottle, stir for 2.5h under nitrogen protection, set the speed to 50 rpm, then heat the reaction to 50℃, increase the speed to 300 rpm, and after 10 hours, take the liquid sample for Fourier infrared absorption spectrum test. The analysis results show that the hydrolysis reaction reaches 99%, the reaction is complete, cool to 25-35℃, filter out NH2-UiO-66 (can be recovered), and the characterization results are shown in Figure 5 .
[0061] Step 3: Drop the filtrate into pure water to precipitate a white precipitate. Stir mechanically at a speed of 25 rpm, filter under reduced pressure to obtain a solid white product, and slurry it with pure water three times. Filter and dry to obtain the final product. Nuclear magnetic hydrogen spectrum test analysis shows that only poly(p-acetoxystyrene) undergoes hydrolysis reaction, and the product is consistent with the target product. The characterization results can be found in Figure 4 . Through GPC test, the product Mw = 10203, PDI = 1.511. The yield is 90%, and the characterization results are shown in Figure 6 .
[0062] Example 3
[0063] Step 1: Put 70g of p-acetoxystyrene and 30g of styrene into a 2L four-necked bottle equipped with a condenser, a thermometer, a nitrogen inlet, and an electric stirrer, and add 4g of AIBN (azobisisobutyronitrile) and 450g of ethanol. After stirring for two hours under nitrogen protection, heat to 70°C and keep the temperature for 18 hours. Dissolve, precipitate, and filter to obtain a white precipitate, which is a binary copolymer of p-acetoxystyrene and styrene.
[0064] Step 2: Add the above white precipitate, 10g pure water and 1mg NH2-UiO-66 to another four-necked bottle, stir for 2.5h under nitrogen protection, set the speed to 50 rpm, and gradually increase the speed to 300 rpm. The reaction temperature was raised to 50℃. After 10 hours, the liquid sample was taken out for Fourier infrared absorption spectrum test. The analysis results showed that the hydrolysis reaction reached 99%. The reaction was cooled to 25-35℃, and NH2-UiO-66 was filtered out (can be recycled). The characterization results are shown in Figure 8 .
[0065] Step 3: Drop the filtrate into pure water to precipitate a white precipitate. Stir mechanically at a speed of 25 rpm, filter under reduced pressure to obtain a solid white product, and beat with pure water three times. Filter and dry to obtain the final product. Nuclear magnetic hydrogen spectrum test analysis shows that poly(p-acetoxystyrene) undergoes hydrolysis reaction, and the product is consistent with the target product. The characterization results can be found in Figure 7 . Through GPC test, the product Mw = 10807, PDI = 1.515. The yield is 96%. The characterization results are shown in Fig. 9 .
[0066] Example 4
[0067] Step 1: Put 70g of p-acetoxystyrene, 10g of styrene, and 20g of tert-butyl acrylate into a 2L four-necked bottle equipped with a condenser, a thermometer, a nitrogen inlet, and an electric stirrer, and add 4g of AIBN (azobisisobutyronitrile) and 450g of ethanol. After stirring for two hours under nitrogen protection, heat to 70°C and keep warm for 18h. Dissolve, precipitate, and filter to obtain a white precipitate, which is a terpolymer of p-acetoxystyrene, styrene, and acrylate.
[0068] Step 2: Add the above white precipitate, 10g pure water and 1mg NH2-UiO-66 to another four-necked bottle, stir for 2.5h under nitrogen protection, set the speed to 50 rpm, and gradually increase the speed to 300 rpm. The reaction temperature was raised to 50℃. After 10 hours, the liquid sample was taken out for Fourier infrared absorption spectrum test. The analysis results showed that the hydrolysis reaction reached 99%. The reaction was cooled to 25-35℃, and NH2-UiO-66 was filtered out (can be recycled). The characterization results are shown in Fig.11 .
[0069] Step 3: Drop the filtrate into pure water to precipitate a white precipitate, filter under reduced pressure to obtain a solid white product, and slurry it with pure water three times. Filter and dry to obtain the product. Nuclear magnetic hydrogen spectrum test analysis shows that only poly(p-acetoxystyrene) undergoes hydrolysis reaction, and the product is consistent with the target product. The characterization results can be found in Fig.10 . Through GPC test, the product Mw = 10081, PDI = 1.613. The yield is 85%. The characterization results are shown in Fig.12 .
[0070] The MOFs catalysts described in the embodiments of the present application are amino MOFs catalysts and sulfonic acid MOFs materials. MOF-808-NH2, NH2-Uio-66, Mil-101-Cr-NH2 produced by Xi'an Qiyue Biotechnology Co., Ltd. and NH2-UIO-66 (hafnium) produced by Shanghai Kaishu Chemical Technology Co., Ltd., and MIL-101(Cr)-SO3H and UIO-66-SO3H produced by Bid Pharmaceuticals can be selected.
[0071] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing PHS resin for photoresist by selective hydrolysis, characterized in that: The following steps are involved: Step 1, adding poly(p-acetoxystyrene) or poly(p-acetoxystyrene) copolymer, MOFs catalyst, water and solvent into a reactor to obtain a mixed solution; Step 2, at room temperature, initially mechanically stir the mixed solution obtained in step 1, introduce nitrogen into the system for purging, mechanically stir for 2 h-3 h under nitrogen purging, increase the mechanical stirring speed, and heat the system to the reaction temperature; Step 3, after the reaction is completed, the reaction solution is filtered under reduced pressure to obtain a filtrate, and the obtained filtrate is slowly dripped into pure water, the product is slowly precipitated, and the pure water is in a mechanical stirring state; Step 4: After the reaction liquid is added, the precipitate is obtained and stirring is continued for 2 h. Step 5, filtering the precipitate under reduced pressure, taking the filter residue, and drying it in a vacuum oven to obtain a pure white product poly(p-hydroxystyrene) and its copolymer resin, and performing characterization tests on the product.
2. The preparation method according to claim 1, characterized in that: The poly(p-acetoxystyrene) copolymer includes: a p-acetoxystyrene monomer, a binary copolymer of p-acetoxystyrene and styrene, a binary copolymer of p-acetoxystyrene and acrylate, a terpolymer of p-acetoxystyrene, styrene and acrylate, and a terpolymer of p-acetoxystyrene, 1-(1-ethoxyethoxy)-4-vinylbenzene and tert-butyl (4-vinylphenyl) carbonate.
3. The preparation method according to claim 1, characterized in that: The MOFs catalysts are amino MOFs catalysts and sulfonic acid MOFs materials, including: MOF-808-NH2, NH2-Uio-66, Mil-101-Cr-NH2, NH2-UIO-66 (Hafnium), MIL-101 (Cr) -SO3H, UIO-66-SO3H.
4. The preparation method according to claim 1, characterized in that: The solvent in step 1 is an electronic grade solvent including: methanol, ethanol, isopropanol, tetrahydrofuran, tert-butyl methyl ether, n-heptane, cyclohexane, toluene, xylene, ethyl acetate, DMF, DMSO, and NMP.
5. The preparation method according to claim 1, characterized in that: The molar ratio of the poly(p-acetoxystyrene) or poly(p-acetoxystyrene) copolymer, the MOFs catalyst, pure water and the solvent is 1:0.1%-0.5%:1:5-10.
6. The preparation method according to claim 1, characterized in that: In the step 2, the mechanical stirring speed under nitrogen purge is 47-54 rpm, and the mechanical stirring speed after increasing the mechanical stirring speed is 295-305 rpm; in the step 3, the mechanical stirring speed of pure water during precipitation is 22-28 rpm.
7. The preparation method according to claim 1, characterized in that: The reaction temperature in step 2 is 50°C-80°C.
8. The preparation method according to claim 1, characterized in that: The pure water is electronic grade pure water, which is distilled in a cleanliness level 1,000 laboratory for future use, and needs to be deoxygenated before use to ensure that the dissolved oxygen content in the water is extremely low.
9. Poly(p-hydroxystyrene) and its copolymer resin for photoresist obtained by the preparation method according to claim 1.
10. Use of the poly(p-hydroxystyrene) and its copolymer resin according to claim 9 in the preparation of photoresist.
Citation Information
Patent Citations
Styrene derivative-methacrylate copolymer containing photo-acid generation groups as well as preparation and application of styrene derivative-methacrylate copolymer
CN105669889A
Dietary supplement derived from fermented milks for the prevention of osteoporosis
CN1300187A